Influence of the solvent on the sensitization of nanostructured electrodes of TiO2 for solar cells sensitized with a natural dye extracted from purple corn: Molecular dynamic simulation and experimental validation - Huamán Aguirre, Arnold Anthony (2024)
This study uses molecular dynamics (MD) simulations and experiments to explore the interaction between titanium dioxide (TiO2) and cyanidin-3-glucoside (C3G), the main compound in purple corn, in the context of sensitized solar cells. dyes (DSSCs). Different proportions of water and ethanol in the solvent were applied. MD revealed the effective chemisorption of C3G and significant variations in the equilibrium enthalpy, indicating the influence of the solvent composition on the stability of the TiO2/C3G system. The negative adsorption energies (EAds) reveal favourable adsorption processes. A possible formation of solvation shells was observed near the TiO2 nanoparticle. The experimental results supported the simulation predictions, highlighting the system with 25 % water and 75 % ethanol (W1E3) as the most efficient. The formation of solvation shells facilitates C3G adsorption, improving anchoring and reducing unwanted electron recombinations. The results provide essential information for the selection of optimal solvents in future photovoltaic applications, contributing to the improvement of the performance of these solar cells.